Konstruktionen literarischer Authentizität in autobiographischen Erzähltexten - Schmidt, Nadine Jessica (V&R unipress, 2014)
The study consists of two focus areas: On the one hand it deals with the complex matter of the “construction of literary authenticity” – therefore with a yet open, recent topic of research – and exposes the problem of the term “autofiction”, which is recently used in the research literature about autobiography. On the other hand the problem of authenticity is exemplary unfolded on the basis of the paradigm of four differently conceived autobiographic narrative texts, which have been published since the 1970: Christa Wolfs ,“Kindheitsmuster”, Ruth Klügers “weiter leben. Eine Jugend”, Binjamin Wilkomirskis “Bruchstücke. Aus einer Kindheit 1939-1945” and Günter Grass' “Beim Häuten der Zwiebel”.
Literaturverzeichnis: Seite 277-303. - Seite 277 nicht paginiert
Keywords: Authentizität; Autobiographie; Gegenwartsliteratur; Literatur; Literaturgeschichte /Deutschland; Literaturgeschichte nach 1945; Grass; Günter; Klüger; Ruth; Stein; Benjamin; Wilkomirski; Binjamin; Wolf; Christa